Phenotyping Studies to Assess the Effects of Phytopharmaceuticals on In Vivo Activity of Main Human Cytochrome P450 Enzymes - Zadoyan, Gregor; Fuhr, Uwe (Planta Medica, 2012)
The extensive use of herbal drugs and their multiple components and modes of action suggests that they may also cause drug interactions by changing the activity of human cytochrome P450 enzymes. The purpose of the present review is to present the available data for the top 14 herbal drug sales in the U. S. Studies describing the effects of herbal drugs on phenotyping substrates for individual CYPs were identified by a comprehensive MEDLINE search. Drugs included Allium sativum (Liliaceae), Echinacea purpurea (Asteraceae), Serenoa repens (Arecaceae), Ginkgo biloba (Ginkgoaceae), Vaccinium macrocarpon (Ericaceae), Glycine max (Fabaceae), Panax ginseng (Araliaceae), Actea racemosa (Ranunculaceae), Hypericum perforatum (Hypericaceae), Silybum marianum (Asteraceae), Camellia sinensis (Theaceae), Valeriana officinalis (Valerianaceae), Piper methysticum (Piperaceae), and Hydrastis canadensis (Ranunculaceae) preparations. We identified 70 clinical studies in 69 publications. The majority of the herbal drugs appeared to have no clear effects on most of the CYPs examined. If there was an effect, there was mild inhibition in almost all cases, as seen with garlic or kava effects on CYP2E1 and with soybean components on CYP1A2. The most pronounced effects were induction of CYP3A and other CYPs by St. Johnʼs wort and the inhibitory effect of goldenseal on CYP3A and CYP2D6, both being borderline between mild and moderate in magnitude. With the exceptions of St. Johnʼs wort and goldenseal, the information currently available suggests that concomitant intake of the herbal drugs addressed here is not a major risk for drugs that are metabolized by CYPs.
Keywords: cytochrome P450; cocktail interaction studies; herb-drug interaction; phytopharmaceuticals; botanicals; herbal products